An Expensive Multi-Objective Evolutionary Algorithm with RBF-IDW Surrogate Model - Liu, Yuhao; Fang, Hongyi; Li, Fei (2024 International Conference on New Trends in Computational Intelligence (NTCI), 2024)
In surrogate-assisted multi-objective evolutionary optimization, surrogate models provide approximations for each solution on each objective, with varying quality. In the proposed algorithm, the RBF-IDW surrogate model replaces the Gaussian process model used in the original algorithm, constructing a model for each objective function and identifying candidate solutions during the optimization phase. A Gaussian process model is then used to approximate performance indicators measuring convergence and diversity. Finally, the solution with the maximum expected improvement is selected and evaluated using the expensive objective function. The algorithm's feasibility is demonstrated through tests on the DTLZ and WFG suites.